Pengaruh Good Corporate Governance dan Environmental Performance Terhadap Pengungkapan Islamic Social Reporting pada Perusahaan Sektor Pertambangan yang Terdaftar di Jakarta Islamic Index Periode 2019-2024 - Rara Hardianti; Tulus Suryanto; Citra Etika (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the effect of Good Corporate Governance (GCG) and Environmental Performance on Islamic Social Reporting (ISR) disclosure in mining sector companies listed in the Jakarta Islamic Index (JII) during the 2019–2024 period. This research employed a quantitative approach with a causal associative design. The data used were secondary data obtained from annual reports, sustainability reports, and the Environmental Performance Rating Program (PROPER) issued by the Ministry of Environment and Forestry. The sample consisted of five mining companies selected using purposive sampling. Data were analyzed using panel data regression with the Common Effect Model (CEM) through EViews 13, supported by descriptive statistics, classical assumption tests, t-test, F-test, and coefficient of determination. The results indicate that Good Corporate Governance has a positive and significant effect on Islamic Social Reporting disclosure. Likewise, Environmental Performance has a positive and significant effect on Islamic Social Reporting. Simultaneously, both independent variables significantly influence Islamic Social Reporting, with an Adjusted R² value of 82.44%, indicating that the model explains most of the variation in ISR disclosure. These findings imply that effective corporate governance and better environmental performance encourage companies to disclose social responsibility information based on Islamic principles more comprehensively, thereby strengthening corporate accountability and transparency toward stakeholders..